KOMUNIKASI POLITIK SINGAPURA: (Studi Terhadap Adaptasi Budaya) - Abdul Rani Usman; Azman Sulaiman; Teuku Zulyadi; Hanifah Nurdin (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Singapore is a pluralistic nation consisting of various ethnicities. The majority of ethnic groups are Chinese, Malay, Indian. As a city-state that was only independent in 1965, it has various potentials, including the potential for reliable human resources. The state of Singapore was originally a Malay territory, the Sultanate of Johor. However, the area was in dispute with England. After Japan occupied Tamasek or Singapore, Singapore's sovereignty became irregular. After Japan lost to the Allies, power in Singapore became vacant. However, after independence, Singapore became a country ruled by the Prime Minister, Lee Kuan Yew. The Singapore government is of global concern because the Malay mainland is held by ethnic Chinese. This fame was coupled with the cleverness of Lee Kuan Yew's thinking in running a political system that accentuated various modern thoughts. This article uses the Agenda Setting Theory and Content Analysis methods. This paper shows that Singapore's Political Communication adapted to Chinese, Western and Malay thinking.